1990
DOI: 10.1002/dev.420230103
|View full text |Cite
|
Sign up to set email alerts
|

Premature visual stimulation accelerates intersenory functioning in bobwhite quail neonates

Abstract: Recent evidence from both altricial and precocial neonates suggests that premature stimulation of a later developing sensory system may alter the functioning of earlier developing sensory systems. The present study examined the influence of prenatal visual stimulation on postnatal auditory functioning in precocial bobwhite quail chicks. Hatchlings that experienced patterned light during the 24-36 hr prior to hatching did not exhibit a naive auditory preference for their species-specific maternal call at 24 hr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
7
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 95 publications
(127 citation statements)
references
References 25 publications
5
114
7
1
Order By: Relevance
“…27,32 Animal studies suggest that the timing of sensory exposures may be as important to development as the type of sensory stimulation. [33][34][35][36][37]43 For example, auditory cues seem to have functional priority over visual ones in early development in precocial birds. 28,[38][39][40][41][42] Term newborn infants tested at 6 months of age demonstrated an auditory dominance, 44 with a progression to visual dominance by adulthood.…”
Section: Processes Of Neurosensory Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…27,32 Animal studies suggest that the timing of sensory exposures may be as important to development as the type of sensory stimulation. [33][34][35][36][37]43 For example, auditory cues seem to have functional priority over visual ones in early development in precocial birds. 28,[38][39][40][41][42] Term newborn infants tested at 6 months of age demonstrated an auditory dominance, 44 with a progression to visual dominance by adulthood.…”
Section: Processes Of Neurosensory Developmentmentioning
confidence: 99%
“…Early or enhanced visual experiences may lead to the accelerated development of the visual system with an associated decline in auditory or chemosensory responsiveness. 36,46,47 Some species-specific range of normal exposure exists, and deviations of exogenous stimuli above or below this range, or with atypical timing, may negatively impact or alter typical perceptual development. 47,[48][49][50][51] Term newborns exposed to light with auditory pre-stimulation had a subsequent preference for lower light stimulation compared to babies who did not have increased auditory stimulation.…”
Section: Processes Of Neurosensory Developmentmentioning
confidence: 99%
“…Figure 9 shows the mean PTD for the Trained Controls and the Visual conditions and Figure 10 shows the mean PTE for the Trained Controls and the Visual conditions. Previous studies have indicated that bobwhite quail embryos presented with patterned visual stimulation during the last 2-3 days before hatching do not demonstrate species-typical perceptual development (Lickliter, 1990a). While unmanipulated control chicks showed preference for the bobwhite maternal call at 24 or 48 hours post hatch using only auditory information, chicks that were presented with visual stimulation prenatally needed both bobwhite auditory and visual cues to make the same discrimination.…”
Section: Resultsmentioning
confidence: 86%
“…In a similar study, Lickliter (1990a) found that bobwhite quail embryos that were presented with continuous patterned visual stimulation during the 24-36 hours before hatching required auditory (maternal call) and visual cues (stuffed bobwhite hen model) to demonstrate a preference for their species typical maternal call when tested at 24 or 48 hours post hatch. In contrast, unmanipulated control chicks were able to show preference for the maternal call at 24 and 48 hours post hatch using only auditory information.…”
Section: The Effects Of Altering the Timing Of Premature Stimulationmentioning
confidence: 91%
“…Studies have examined behaviors such as perceptual learning and emotional reactivity in quail and found quite interesting results (Lickliter, 2005). For example, Lickliter (1989) found that exposing bobwhite quail embryos to patterned visual stimulation in the period immediately prior to hatching interfered with species typical auditory preferences in the post-hatch period. In contrast, another study examining the effects of prenatal auditory stimulation on bobwhite quail embryos showed enhanced postnatal responsiveness.…”
Section: Oxytocin Social Cognition and Stress Responsivenessmentioning
confidence: 99%